Digital learning models: experience of online learning during the pandemic - Muzayanah, Umi; Maknun, Moch Lukluil; Sa'ad, Faidus; Mustolehudin, Mustolehudin; Taruna, Mulyani Mudis (International Journal of Evaluation and Research in Education (IJERE), 2025)
During the global pandemic of COVID-19, the learning model has been “forced” to transition from conventional to distance learning. At the beginning of its implementation, digital-based learning received many complaints from teachers, parents, and students. Gradually, they can adapt to distance learning that utilizes many digital devices. Through quantitative and qualitative research approaches, this paper aims to describe the online learning model in schools and Islamic boarding school (pesantren) based on their experience during COVID-19. From these studies, several digital-based learning models can be identified. First, social media-based learning. Social media-based learning is carried out by optimizing the use of WhatsApp as the main media in learning. Second, learning through virtual classrooms, which is face-to-face learning between teachers and students in a digital space. Third, education platform-based learning, where the learning process is conducted through internal school or government platforms. Fourth is blended learning, which is learning partly online and offline. This fourth lesson aims to accommodate the learning needs of students or teachers who have obstacles such as signal difficulties and weak economies. The findings contribute to the availability of references for digital learning models that can be applied in the future.